On Matrix Sequence of modified Tribonacci-Lucas Numbers - Erkan Taşdemir; Yüksel Soykan; Vedat İrge (MANAS: Journal of Engineering)
In this paper, we define modified Tribonacci-Lucas matrix sequence and investigate its properties.